Strategi Pembelajaran Diferensiasi dalam Menghadapi Keberagaman Siswa - Bakar, Abu (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to examine the implementation of differentiated learning strategies in addressing student diversity in elementary school classrooms. The research is qualitative in nature, using a case study approach. The subjects of this research are teachers and students in elementary school, while the object of the study is the implementation of differentiated learning in the context of diversity. Data collection techniques include interviews, observations, and documentation. Data were analyzed using thematic analysis to identify patterns related to the application of differentiation strategies. The results indicate that differentiated learning enhances student motivation and academic performance by providing equitable opportunities based on their abilities and interests. However, the main challenges in its implementation are time and resource limitations. The conclusion is that, despite challenges, differentiated learning proves effective in creating an inclusive classroom that addresses the diverse needs of students.